Hybrid event strategy for the fishing community (Case study of the fisherman community of Beba hamlet, Takalar regency during the Covid-19 pandemic) - Muhammad Sabiq; Asriandi Asriandi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
This study examines the concept of Hybrid Event as a new strategy that is considered reliable enough for fishing communities in Makassar to face new normal conditions. New economic spaces have been created for fishermen and UMKM fishermen who have been affected by Covid-19. The old economic spaces are no longer reliable because they are constrained by laws and regulations from the government that require restrictions on social distancing and physical distancing. The purpose of this study was to analyze the readiness of the fishing community and fishermen UMKM actors in Beba, Tamasaju Village, North Galesong District, Takalar Regency to enter business era 4.0 in the midst of the Covid-19 pandemic and assist the realization of government policies in providing socio-economic protection to fishing communities and as well as UMKM fishermen in Makassar. The resulting output is in the form of four (4) main strategies: first, combining physical and virtual meetings, so that fishermen's businesses and businesses and fishermen's UMKM continue to run in various different atmospheres. Second, health protocols such as maintaining physical distance and social distance are not violated and at the same time the pace of economic activity of fishing communities and fishing UMKM can still run normally. Third, empowering fishing communities and fishing UMKM  in using appropriate information technology. And fourth, the government's budget policy for fishing communities and fishing UMKM that are oriented to the provision of appropriate information technology